CNT/VS2-MoS2 with multi-interface structure for improved hydrogen evolution reaction. Issue 20 (10th February 2021) - Ren, Xianpei; Wei, Qingbo; Wu, Fei; Wang, Yonghua; Zhao, Liangjun
Abstract : CNT/VS2 -MoS2 composites with a multi-interface structure were prepared for the high-efficiency hydrogen evolution reaction. Abstract : CNT/VS2 -MoS2 with a multi-interface structure shows significantly enhanced catalytic activity compared with MoS2, CNT/MoS2, CNT/VS2 and VS2 -MoS2, including a low overpotential of −215 mV at 10 mA cm −2 and a small Tafel slope of 64 mV dec −1 . The enhanced catalytic activity could be ascribed to the multiple interfaces in CNT/VS2 -MoS2, which can promote charge transfer and yield abundant active sites. This study provides a valuable route to improve the catalytic performance of two-dimensional electrocatalysts.